The significance of borderline haemoglobin A₂ level among Kelantan population - Sehat, Nani Shahida (2016)
About 3-5% of Malaysians are thalassaemia carriers. Thalassaemia diagnosis based on haematological parameters is presumptive thus DNA analysis becomes necessary. Haemoglobin A2 (HbA2) level higher than 4.0% is a classic marker of β-thalassaemia carriers. However, when haematological parameters are suggestive of thalassaemia phenotype but not supported by HbA2 increment, this finding may put the diagnosis into dilemma. This cross sectional study was conducted to determine the proportion of borderline HbA2 level among samples taken for haemoglobin (Hb) analysis in HRPZ II from January 2015 until March 2016. HRPZ II received total of 11,790 samples for thalassaemia screening by CE from all over the state. Samples with HbA2 between 3.0% and 3.9% were selected and their haematological profiles (Hb, MCV, MCH, RBC, RDW and platelets) were analysed and then randomly selected for molecular testing (PCR) for β-gene mutation and α-gene deletion. MARMS-PCR was used for β-globin gene mutation detection while α-globin genes deletion detected by Multiplex Gap-PCR method. From 11,790 samples, 405 (3.4%) samples were found to have HbA2 between 3.0 and 3.9%. Out of that, 117 (28.9%) samples were selected by simple random sampling to proceed with PCR. From 117 samples, 45 (38.5%) showed positive molecular result in which 36 (30.8%) showed β-globin gene mutations, 8 (6.8%) showed α-globin gene deletions and 1 sample (0.9%) showed coexistence of α- and β-globin gene mutations. Out of these 37 samples with β-globin gene mutations, 32 (86.5%) had single gene defect while 5 (13.5%) had two gene mutations. The commonest of single β-gene mutation detected were Cd 19 (A-G) (45.9%), followed by IVS 1-1 (G-A) (24.3%), Poly A (13.5%) and CAP +1 (A-C) (2.7%). There was statistically significant association between HbA2 levels and positive molecular result. Interestingly, this study also showed 10 (27.0%) positive β-gene mutation even though the HbA2 level was normal at only 3.0%. There was significant number of people with borderline HbA2 and confirmed as thalassaemia carriers by PCR. This study revealed an important finding to consider revision of HbA2 range and haematological parameters that should prompt for DNA analysis in case of borderline HbA2 for the success of thalassaemia screening programme in our population.